Strategi Guru PAI dalam Meningkatkan Pengamalan Beragama Siswa di SMA Negeri 3 Padang Panjang (Jurnal Riset Rumpun Agama dan Filsafat, 2026)
This study aims to identify the strategies implemented by Islamic Religious Education (PAI) teachers to enhance students’ religious practice at SMA Negeri 3 Padang Panjang. The research employed a descriptive qualitative method, collecting data through interviews and documentation. The findings reveal that PAI teachers’ strategies include giving reprimands, advice, and warnings; guiding students through religious activities such as Quran memorization (tahfiz), Islamic student organizations (rohis), congregational prayers, and other worship practices; and collaborating with parents and fellow teachers. Supporting factors include the encouragement provided by the school and parents, while inhibiting factors involve students’ lack of awareness and their family background.